Twentieth Fungal Genetics Conference Scientific Program - Fungal Genetics Conference (Fungal Genetics Reports, 1999)
Abstracts are published as an electronic supplement to Fungal Genetics Newsletter # 46 and should be cited as follows: Fungal Genet. Newsl. 46S: Abstract Number